Rāingān kānwičhai r̄ưang kānsangkhr̨o ngān wičhai kīeokap kānrīan kāns̨ōn klum thaksa (Khanittasāt) radap prathommasưksā (ʻĒkkasān rāingān wičhai thāng kānsưksā, 1995)
Research analysis on Thai education at primary level schools in Thailand.